L'île-enfant, sur le symbolisme littéraire de l'insularité - Stanilewicz, Grażyna (Verbum – Analecta Neolatina, 2008)
This paper deals with the polysemous notion of 'island'. Based on the works of Le Clézio, Tournier, Verne and others, we try to discover the most important levels of interpretation one by one. We will conclude that the representation of the character of the child is very similar to an island.